ASPEK PSIKIATRI DALAM UPACARA MEGEDONG-GEDONGAN - G. A. Ade Cahayani Saraswati; Cokorda Bagus Jaya Lesmana; Ni Ketut Putri Ariani; Luh Nyoman Alit Aryani (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
ABSTRACT Pregnancy is a period of biological, psychological, and social transition that increases women’s vulnerability to mental health disorders, particularly perinatal anxiety and depression. Although various biomedical approaches have been developed, they have not fully addressed the psychosocial and cultural aspects influencing maternal well-being. In Balinese culture, the Megedong-gedongan (Garbha Wedana) ceremony is a pregnancy ritual rich in spiritual and social meaning and involves family and community participation. The purpose of this article is to examine the role of the Megedong-gedongan ceremony on maternal mental health from a cultural psychiatry perspective. The method used is a literature study with a descriptive qualitative approach through a search of scientific journal articles, reference books, and policy documents related to perinatal mental health and cultural practices of pregnancy published between 2016 and 2025. The research stages include identification and selection of literature, critical review of content, grouping themes, and synthesis and interpretation of results within a cultural psychiatry framework. The results indicate that the Megedong-gedongan ceremony acts as a form of social support that includes emotional, informational, and practical support, which has the potential to reduce stress and anxiety levels in pregnant women and increase psychological readiness for childbirth. This study affirms that Megedong-gedongan constitutes a relevant socio-cultural capital for promoting the mental health of pregnant women and has the potential to be integrated into culturally sensitive maternal healthcare approaches. ABSTRAK Kehamilan merupakan masa transisi biologis, psikologis, dan sosial yang meningkatkan risiko gangguan kesehatan mental, khususnya kecemasan dan depresi perinatal. Meskipun pendekatan biomedis telah dikembangkan, aspek psikososial dan budaya belum sepenuhnya terakomodasi. Dalam budaya Bali, upacara Megedong-gedongan (Garbha Wedana) merupakan ritual kehamilan bermakna spiritual dan sosial yang melibatkan keluarga serta komunitas. Tujuan penulisan artikel ini adalah untuk mengkaji peran upacara Megedong-gedongan terhadap kesehatan mental ibu hamil dari perspektif psikiatri budaya. Metode yang digunakan adalah studi literatur dengan pendekatan kualitatif deskriptif melalui penelusuran artikel jurnal ilmiah, buku rujukan, dan dokumen kebijakan terkait kesehatan mental perinatal dan praktik budaya kehamilan yang terbit dalam rentang tahun 2016–2025. Tahapan penelitian meliputi identifikasi dan seleksi literatur, telaah kritis isi, pengelompokan tema, serta sintesis dan pemaknaan hasil dalam kerangka psikiatri budaya. Hasil kajian menunjukkan bahwa upacara Megedong-gedongan berperan sebagai bentuk dukungan sosial yang mencakup dukungan emosional, informasional, dan praktis, yang berpotensi menurunkan tingkat stres dan kecemasan ibu hamil serta meningkatkan kesiapan psikologis menghadapi persalinan. Penelitian ini menegaskan bahwa Megedong-gedongan merupakan modal sosial-budaya yang relevan untuk promosi kesehatan mental ibu hamil dan berpotensi diintegrasikan dalam pendekatan layanan kesehatan maternal yang sensitif budaya.